Family-based intervention for adolescents with substance use disorders in Vietnam. (December 2021) - Nguyen, Thu Trang; Dinh, Thi Thanh Thuy; Busse, Anja; Kashino, Wataru; Suhartono, Sanita; Le, Minh Giang
Abstract: Background: Adolescent substance use is a leading risk factor of medical and social problems in adults. However, evidence-based interventions for substance use disorders (SUD) among youth in resource-limited countries are lacking. Treatnet Family (TF), developed by United Nations Office on Drugs and Crime (UNODC), aims to make youth SUD care more affordable and accessible in low- and middle-income countries. This study explores the suitability of TF in Vietnam. Method: Twenty interviews were conducted with eight adolescents and their family members who participated in TF, and four practitioners who delivered TF. Questions centred on their experiences with the intervention and suggestions for improvement. Thematic analysis was used to evaluate the data. Results: All adolescents were male with an average age of 19.3. Seven of them had left school. Most caregivers were female. Both family members and adolescents expressed a great demand for support, and both groups appreciated the immediate improvement in parent–child communication. However, the impact of TF could be compromised due challenges in recruiting families, possibly arising from the novelty of a family-based intervention in Vietnam and drug-related stigma. The perception of drug use as an acute condition instead of a chronic disorder, and the lack of a continuing care system, also made it difficult to retain participants. Conclusion: Vietnamese adolescents with SUD and their family members were in great need of support and access to evidence-based interventions. Building a comprehensive, health-centred substance use disorder treatment and care system would enhance treatment impact. Highlights: Vietnamese families with SUD are in great need for therapeutic support. Treatnet Family produces a positive impact on parent-children communication. Recruitment barriers: stigma and low treatment motivation. Building a comprehensive system of care would enhance intervention impact.